2019
DOI: 10.1186/s13058-019-1171-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling molecular regulators of recurrence in chemorefractory triple-negative breast cancers

Abstract: Background Approximately two thirds of patients with localized triple-negative breast cancer (TNBC) harbor residual disease (RD) after neoadjuvant chemotherapy (NAC) and have a high risk-of-recurrence. Targeted therapeutic development for TNBC is of primary significance as no targeted therapies are clinically indicated for this aggressive subset. In view of this, we conducted a comprehensive molecular analysis and correlated molecular features of chemorefractory RD tumors with recurrence for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…Accordingly, several studies have shown ADAM12 mRNA overexpression in chemo-resistant ER-negative breast tumours [40,41]. In addition, ADAM12 re-expression in the non-malignant breast epithelial MCF 10A cell line has been reported to induce resistance to cisplatin [42], while ADAM12 silencing facilitates 5-fluorouacil sensitivity in a TNBC xenograft model [39]. Consistent with these findings, paclitaxel administration has been shown to increase ADAM12 protein levels in the SUM159PT TNBC cell line [37].…”
Section: Discussionmentioning
confidence: 63%
“…Accordingly, several studies have shown ADAM12 mRNA overexpression in chemo-resistant ER-negative breast tumours [40,41]. In addition, ADAM12 re-expression in the non-malignant breast epithelial MCF 10A cell line has been reported to induce resistance to cisplatin [42], while ADAM12 silencing facilitates 5-fluorouacil sensitivity in a TNBC xenograft model [39]. Consistent with these findings, paclitaxel administration has been shown to increase ADAM12 protein levels in the SUM159PT TNBC cell line [37].…”
Section: Discussionmentioning
confidence: 63%
“…The tested expression variants allow the generation of two tumor categories; one includes tumors with higher differentiation, high Ki67, and low TGFß and MEK activity, while the second agglutinates those tumors enriched in genes related to invasive pathways and poor differentiation. Consistent with the stem-like phenotype typically induced by the latter and already related to residual disease [ 83 ], this group is characterized by enhanced MEK and TGFß activation, together with the deletion of DUSP4 [ 80 , 84 , 85 , 86 ]. In line with this, additional studies focused on the TN subtype reported the reduction in DUSP4 expression in RD as related to poor RFS ( p < 0.0004) [ 84 ].…”
Section: Residual Diseasementioning
confidence: 82%
“…In the analysis of 75 TN RD arising from a phase II trial (BRE09-146), it was observed that the most abundant mutations were also in TP53 (88%), followed by PIK3CA mutations (11%). Regarding the CNA profile of RD, they identified gains in MCL1 , MYC , and GATA3 , and losses in BRCA2 , FLT3 and RB1 , with the most frequently amplified gene being MYC (24% of cases) and the most frequently depleted gene BRCA2 (68% of cases) [ 83 ]. In addition, the analysis of 18 matched pre-NAC vs. post-NAC matched samples showed a mutational homogeneity between both scenarios, given that 13 out of the 18 matched samples had identical mutational profiles.…”
Section: Residual Diseasementioning
confidence: 99%
See 2 more Smart Citations